Tradisi “Ngobeng”; Sebuah Kearifan Lokal yang Hampir Punah - Fitriah Fitriah (Fakultas Adab dan Humaniora UIN Raden Fatah, 2019)
Introduction. This article intends to provide an overview of the existence of the ngobeng tradition in seri bandung village, tanjung batu district, ogan ilir regency and the values ​​of local skills which are still relevant to the community today. Data collection method. In collecting data, this research uses the method of observation, interview and documentationAnalysis data. In carrying out this analysis the researchers used qualitative analysis techniques, namely analysis of qualitative data by collecting data, editing data that had been collected, then classifying the respondents' answers, after which they then interpreted (interpreted) data that had been collected through the subject matter. Results and discussion. The tradition of ngobeng is a hereditary tradition that has wisdom values ​​that are still relevant to be preserved by society today. Among the values ​​contained in the tradition of ngobeng include; the value of togetherness, mutual assistance, and respect. Although in most areas this tradition has begun to be abandoned due to the current of globalization with the existence of a more practical buffet pattern, but in seri bandung village, tanjung batu district, ogan ilir regency, this tradition is still preserved both in marriages, circumcisions, and etcConclusion. The tradition of ngobeng is still very relevant to be preserved i, this is because in the tradition of ngobeng there are values ​​of wisdom that are positive in dealing with the current problematic issues.